Leaving children without reasonable care and supervision: Between law and reality in Malaysia - Mohd Yusoff, Jal Zabdi (UUM COLGIS Universiti Utara Malaysia, 2009)
Parents and guardians have a moral as well as a legal duty to exercise reasonable care and supervision on their children. Unfortunately, whether we realize it or not, there are several acts and omissions committed by these parents or guardians which are detrimental to the child concerned. One such omission is where the child is left without any reasonable care and supervision by his or her parents or guardian. Data and reports show that there are a number of reported cases of children being left without reasonable care and supervision which have resulted in casualties. Most of these reported cases show that the children were either trapped in their own houses or cars as a result of being locked from the outside by their parents or guardian. Due to the increase in the number of such cases, the legislature has made leaving children without reasonable care and supervision by the parents or guardian an offence under the Child Act 2001. Although it is an offence to leave children without reasonable care and supervision, it is sad to note that there are still cases where children are being left unattended for various reasons. Hence, the purpose of this paper is to examine the abovementioned problem as well as to look at the same from the perception of the respondents based on the research that has been conducted.